Connecting the Dots of Care: A pilot study linking Aboriginal and/or Torres Strait Islander peoples with diabetes care in hospital, using hospital pharmacists - Susan Welch; Rebekah Moles; Alexander Viardot; Pauline Deweerd; Scott Daly; Kylie Lee (Exploratory Research in Clinical and Social Pharmacy, 2023)
Background: Diabetes is common among Aboriginal and/or Torres Strait Islander peoples, yet often undetected in hospital. Objective: To identify how urban hospital pharmacists can detect if Aboriginal and/or Torres Strait Islander patients have diabetes or a higher chance of getting diabetes. Methods: A multi-methods study used data from patients, and researcher field notes. Aboriginal and/or Torres Strait Islander peoples admitted to hospital over 12-weeks (July–October 2021) were prospectively identified from admissions lists. A hospital pharmacist-researcher visited eligible patients. Consenting participants had their blood glucose and HbA1c checked. Participants with HbA1c > 6.5% (no known diabetes) or 7% (known diabetes) were referred for endocrinology review during their stay. Test results and resultant diabetes plan were shared with their general practitioner. Two days after discharge, participants were called to gauge views on their hospital-based diabetes care. Barcode technology recorded pharmacist time. Voice-recorded field notes were thematically analysed. Ethics approval was obtained. Results: Seventy-two patients were eligible for inclusion, 67/72 (93%) consented to take part. Sixty-one (91%) patients returned a HbA1c < 6.5, of which, 4/61 (6.5%) returned a HbA1c, 6–6.4. They were contacted to yarn about diabetes prevention. Six of the 67 (9%) qualified for endocrine review, 5 had known diabetes, one newly diagnosed. None were known to endocrinology. All participants telephoned were satisfied with their hospital-based diabetes care. Pharmacist time for initial introductory yarn, consenting process, organisation of HbA1c and results discussion was 20 min or 40 min if referred for endocrine review. Field notes guided understanding of service implementation. Conclusion: This novel pharmacist-led diabetes screening service for Aboriginal and/or Torres Strait Islander peoples appeared to provide a unique opportunity for screening and referral links in a holistic way. Future research is required to test this model by upscaling to include more pharmacists and other chronic disease screening and referral pathways.